Biological synthesis of ursodeoxycholic acid - Song, Peng; Zhang, Xue; Feng, Wei; Xu, Wei; Wu, Chaoyun; Xie, Shaoqing; Yu, Sisi; Fu, Rongzhao (Frontiers in Microbiology, 2023)
Ursodeoxycholic acid (UDCA) is a fundamental treatment drug for numerous hepatobiliary diseases that also has adjuvant therapeutic effects on certain cancers and neurological diseases. Chemical UDCA synthesis is environmentally unfriendly with low yields. Biological UDCA synthesis by free-enzyme catalysis or whole-cell synthesis using inexpensive and readily available chenodeoxycholic acid (CDCA), cholic acid (CA), or lithocholic acid (LCA) as substrates is being developed. The free enzyme-catalyzed one-pot, one-step/two-step method uses hydroxysteroid dehydrogenase (HSDH); whole-cell synthesis, mainly uses engineered bacteria (mainly Escherichia coli) expressing the relevant HSDHs. To further develop these methods, HSDHs with specific coenzyme dependence, high enzyme activity, good stability, and high substrate loading concentration, P450 monooxygenase with C-7 hydroxylation activity and engineered strain harboring HSDHs must be exploited.